Pendampingan Konservasi Budaya dalam Mempertahankan Kekayaan Budaya di SMK Teuku Umar Semarang - Fauzan, Muhammad Hendrie (TAFANI: Jurnal Pengabdian Masyarakat, 2023)
Preserving culture plays a role in preserving environmental sustainability and social ecosystems. Cultural traditions embody the values of sustainability, both in human relations and in human interaction with the environment. The younger generation, students and students, who are actively engaged in the preservation of culture will also be more likely to be responsible agents of change because they will understand the importance of preserving cultural heritage for the survival of mankind and the planet. This article outlines the role of young people at SMK Teuku Umar Semarang in preserving the values of tradition and cultural conservation. This article is based on the writer's experience during training and community engagement of cultural conservation at SMK Teukur Umar Semarang. This writing has become important because it is essentially about preserving a culture that is not only about the traditions of the past but also about building a sustainable and harmonious future for all living beings on this earth.